Female Infertility and Assisted Reproduction: Impact of Oxidative Stress– An Update - J. Premkumar, Beena; Agarwal, Ashok (Current Women's Health Reviews, 2012)
Augmented levels of reactive oxygen species (ROS) that overpower the body's antioxidant defenses result in oxidative stress (OS). Physiologically balanced levels of ROS and antioxidants maintain homeostasis in the body and allow for normal physiological processes to proceed. Physiological processes that involve oxygen consumption inevitably produce ROS. However, an overabundance of ROS leads to widespread injury to cells, and can damage DNA, lipid membranes, and proteins. An unfavorable reproductive environment hinders normal physiology secondary to this disruption of homeostasis. Infertility may be attributed to reproductive pathologies, leading to OS. Infertile couples often turn to assisted reproductive techniques (ART) to improve their chances for a successful pregnancy. In vitro techniques create an unfavorable environment for gametes and embryos by exposing them to a surplus of ROS in the absence of enzymatic antioxidant protection that normally exists in vivo. This article will review the currently available literature on the effects of ROS and OS on ART outcomes. The role of antioxidant supplementation of ART culture media continues to be a subject of interest to increase the likelihood for ART success.
Keywords: gametes